Hubungan tingkat pengetahuan tentang backpack safety dengan nyeri punggung pada siswa kelas 5 di Denpasar - Ramadhan, Muhammad; Dinata, I Made Krisna (E-Jurnal Medika Udayana; Vol 7 No 4 (2018): E-Jurnal Medika Udayana, 2018)
Health problems that often interfere with the effectiveness of the learning process of students is back pain. One of the causes of back pain in students is the level of knowledge about backpack safety. This study is aimed to identify correlation between the level of knowledge about backpack safety with back pain at Saraswati Primary School students 1 Denpasar.This study is analytic observational study with the cross sectional design. The number of samples in this study were 81 samples. which is the 5 th grade students Saraswati 1 Denpasar. Selection of the sample in this study used simple random sampling technique. Collected data in this study is using primary data which is obtained through questionnaires Level of Knowledge about Backpack Safety and Back Pain Complaints questionnaire. The results showed that the level of knowledge about backpack safety in 5th grade elementary school most are in the category of low knowledge level is 60.5% and 58% of students in grade 5th elementary school experiencing back pain. From the results of this study concluded that there is a significant correlation between level of knowledge about backpack safety with back pain complaint in 5th grade in Denpasar (p = 0.01). Results of this study are expected to be used as promotional material and education to reduce the risk of back pain in children of primary school age. Keywords: Level of Knowledge About Backpack Safety, Low Back Pain, Elementary School Age Children